Engaging National Professional Society to Combat Postpartum Hemorrhage Using Bundle Approach - A FIGO-SAFOG-OGSB-MGH Project: Experience of Implementation in Bangladesh - Begum, Ferdousi; Haththotuwa, Rohana; Thapa, Kusum; Chowdhury, Sameena; Dewan, Farhana (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Objective: To reduce the incidence and death due to post-partum Hemorrhage (PPH) and capacity building of health service providers by using PPH Emergency response using Bundle Approach. Method: Planning and implementation of WHO formulated PPH Bundles [Active Management of Third Stage of Labour (AMTSL), First response Bundle and Refractory PPH Bundle] by Obstetrical and Gynaecological Society of Bangladesh (OGSB) in 14 different levels of public and private hospitals in Bangladesh. After discussion with International Federation of Gynaecology and Obstetrics (FIGO) and South Asian Federation of Obstetrics and Gynaecology (SAFOG) team, a Memorandum of understanding (MOU) was signed; permission from Ministry of Health and Family welfare (MOHFW) was obtained through Directorate General of Health Services (DGHS) and also from all the institutions. The project period was from November 2019 to September 2022 in a spoke-and-hub fashion. A group of master trainers and a technical advisory group were developed comprising of senior obstetricians and gynecologist of Bangladesh. Data were obtained through record keeping of the respective hospitals and Management Information System (MIS) of DGHS, monitoring was done by OGSB and Massachusetts General Hospital (MGH)-FIGO team. Results: Consultative and planning meetings were organized among OGSB, FIGO, SAFOG and MGH: 16 master trainers, 74 trainers were produced and 740 health service providers (Doctor, Nurses, midwives) and 450 non clinical staffs were trained. All clinical and nonclinical bundles were implemented in 14 facilities in spoke-and-hub fashion. Occurrence of PPH, detection rate of PPH, filling up PPH checklist and debrief forms were improved. Data collection system, understanding about data improved a lot. Facility readiness, team work, data monitoring & supervision, network integration and leadership skills were instituted and shown excellent positive changes. Regular simulations were continued which helped old & new service providers to learn and continue proper use of the clinical and non-clinical interventions. Scale up was planned and continued. Conclusion: PPH emergency response using bundle approach was found to be an important practical way to reduce occurrence, death and disability related to PPH. Needs for surgery has reduced also. Quality of services improved in terms of providing standard care, record keeping and reporting. Regular supervision and monitoring; data management and personal motivation are the challenges. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 98-108